2019
DOI: 10.1139/gen-2018-0178
|View full text |Cite
|
Sign up to set email alerts
|

miRNA transcriptome comparison between muscle and adipose tissues indicates potential miRNAs associated with intramuscular fat in Chinese swamp buffalo

Abstract: The amount of intramuscular fat (IMF) affects the tenderness and juiciness of beef and is an important indicator of beef quality. A few miRNAs involved in IMF deposition have been identified in other livestock. However, in the buffalo, the association between miRNA and IMF has not been reported and the miRNA expression profile remains poorly understood. In this study, small RNA sequencing was performed to characterize the miRNA expression pattern in muscle and adipose tissues using the Illumina platform. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…miRNA-18b-3p, identified by RNA-seq, inhibits chicken intramuscular adipocyte differentiation by targeting ACOT13 (Sun et al, 2019). Some miRNAs have also been identified as DE-miRNAs by previous RNA-seq studies related to lipid deposition, including miR-20b, miR-424-3p, miR-486-5p, and let-7f-3p (Hosui et al, 2017;Gasparotto et al, 2019;Huang et al, 2019;Ylioja et al, 2019). Interestingly, miR-664a and miR-542-5p were shown to play an important role in skeletal muscle development (Cai et al, 2018;Ji et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…miRNA-18b-3p, identified by RNA-seq, inhibits chicken intramuscular adipocyte differentiation by targeting ACOT13 (Sun et al, 2019). Some miRNAs have also been identified as DE-miRNAs by previous RNA-seq studies related to lipid deposition, including miR-20b, miR-424-3p, miR-486-5p, and let-7f-3p (Hosui et al, 2017;Gasparotto et al, 2019;Huang et al, 2019;Ylioja et al, 2019). Interestingly, miR-664a and miR-542-5p were shown to play an important role in skeletal muscle development (Cai et al, 2018;Ji et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the high-density genotypes, a genome-wide association study suggested that PPARG coactivator 1 alpha, hepatocyte nuclear factor 4 gamma, and forkhead box P3 participated in IMF deposition in cattle [ 14 ]. Noncoding RNAs have also been reported to be involved in IMF deposition [ 15 , 16 ]. Although many studies have been performed on this subject, the molecular mechanism governing IMF deposition has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, profiling of fat tissue in cattle revealed 54 fat-specific miRNAs [ 19 ], while 18 miRNAs were concomitant with subcutaneous backfat thickness, with miR-378 showing the highest association [ 20 ]. Regarding marbling correlated miRNA profiling, only a few RNA-sequencing studies [ 21 , 22 , 23 , 24 ] and a microarray experiment [ 25 ] identified divergent miRNAs related to intramuscular fat content. Therefore, profiling of miRNAs in animals with different IMF content is imperative to gain further insight into their potential role in beef fat accretion.…”
Section: Introductionmentioning
confidence: 99%